THE INVESTMENT OPPORTUNITY SET, RASIO KEUANGAN, KEPEMILIKAN SAHAM, UKURAN DAN NILAI PERUSAHAAN - Felicia Angelica; Tjhai Fung Jin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to obtain empirical evidence regarding the influence of profitability, liquidity, leverage, firm size, dividend policy, capital structure, managerial ownership, investment opportunity set on firm value. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2021.This study used a purposive sampling method to determine the criteria for the selected sample. The research samples obtained were 40 manufacturing companies. Multiple regression was used to analyze research data with a total of 120 data. The results obtained in this study show that profitability, leverage, and capital structure have an influence on firm value. Liquidity, firm size, dividend policy, managerial ownership, and investment opportunity set have no influence on firm value.